High-Sensitivity RF Choke-Enhanced Dipole Antenna-Coupled Nb5N6 THz Detector - Jiang, Chengtao; Tu, Xuecou; Wan, Chao; Kang, Lin; Jia, Xiaoqing; Chen, Jian; Wu, Peiheng (Frontiers in Physics, 2021)
In this study, we demonstrate an Nb5N6 THz detector with RF choke-enhanced dipole antenna structure for 0.3 THz detection. The maximum electric field intensity of 218 V/m is obtained by optimizing the parameters of the dipole antenna with RF choke. Compared to a dipole antenna without RF choke, the electric field intensity of that with RF choke is improved by 2.6 times. The RF choke-enhanced dipole antenna-coupled Nb5N6 THz detector is fabricated and characterized. The measured maximum responsivity of the detector is 1100 V/W at 0.308 THz, and the corresponding NEP is 6.4 × 10-12 W/Hz1/2. The measured response time of the detector is as low as 8.46 μs. Furthermore, the detector is applied to a homemade THz transmission imaging system for demonstrating its performance. The THz imaging results of a blade and access card show that the contrast of the blade image is sharp and the components hidden within the access card are clearly visible. This indicates that the Nb5N6 THz detector can be used in THz imaging, particularly in THz active imaging, which will have greater application prospects.